PENGARUH BUDAYA KERJA TERHADAP KEJADIAN KECELAKAN AKIBAT KERJA PADA PROYEK DI SMK SEHATI KABUPATEN KARAWANG - Wendi Darmawan; Chaerani Tri Yuliana; Jumaedi, Jumaedi; Muhidin, Muhidin; Wieke Widhiantika (Bajang Institute, 2024)
This study aims to explore the influence of work culture on the frequency of work accidents in construction projects carried out by construction workers at SMK Sehati, Karawang Regency. A good work culture is seen as a key factor in creating a safe working environment and minimizing accident risks. A quantitative survey method was used to collect data from construction workers, focusing on their perceptions of work culture and compliance with safety procedures, such as the use of Personal Protective Equipment (PPE). The results show that the majority of workers rate the work culture at SMK Sehati as